South Sudan's capability trap: Building a state with disruptive innovation - Greg Larson; Peter Biar Ajak; Lant Pritchett (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2013)
The prevailing aid orthodoxy works well enough in stable environments, but is ill-equipped to navigate contexts of volatility and fragility. The orthodox approach is adept at solving straightforward technical or logistical problems (paving roads, building schools, immunizing children), but often struggles or outright fails when faced with complex, adaptive challenges (fighting corruption, upholding the rule of law, establishing democratic institutions). South Sudan, the world's newest country, presents a post-conflict environment full of complex, adaptive challenges. Prior to the signing of the Comprehensive Peace Agreement in 2005 South Sudan had no formal institutions of self-governance. During the Comprehensive Peace Agreement period and after independence in 2011, foreign development agencies have contributed billions of dollars of aid and technical assistance to 'build capacity' in the nascent Government of South Sudan. The donors utilized approaches and mechanisms of support that at least nominally reflect the prevailing aid orthodoxy. We argue that orthodox state-building and capacity building more or less failed in South Sudan, leaving the world's newest country mired in a 'capability trap' (Andrews et al. 2012). Despite countless trainings, workshops, reforms, and a large corps of foreign technical assistants embedded within state ministries, there is an absence of real change, and the Government of South Sudan now 'looks like a state' but performs as anything but. The challenges presented by this new, complicated, post-conflict country demand innovative approaches to building state capability which go beyond importing 'best practice' solutions while feigning 'client ownership'. We explore one such approach to disruptive innovation that has emerged: Problem Driven Iterative Adaptation. To escape from the world's newest capability trap, South Sudan's government and its international donors must challenge themselves to imagine innovative paths to state-building, which diverge from 'business as usual' and attempt to create something that lasts.
Keywords: H4; K4; L3; O2; 330; state-building; capability; governance; post-conflict; innovation; South Sudan